Characterization of Stomatal Leaf of Herbal Plant Andredera cordifolia (Ten.) Steenis and Gratophyllum pictum (L.) Griff. - Elis Tambaru; Resti Ura'; Mustika Tuwo (Universitas Hasanuddin, 2018)
Research on the characterization of stromata leaves of herbal plants Andredera cordifolia and Gratophyllum pictum in Makassar. This study aims to determine the morphological structure of leaves and stomata leaves that are used as herbal plants. Stomata data was used by acetone to get stomata mold, the data were analyzed descriptively. The result of research show that Andredera cordifolia are anisocytic stomata type, 30 stomata/mm2 abaxial stomata, 512 epidermis/mm2 and 368 epidermis/mm2 abaxial, potato stomata spreading in both leaf surface, bigger abaxial stomata size 887,330 μm , longest abaxial stomata greater than 25 μm and 8.0% stomata index. Gratophyllum pictum type stomata diasistik, stomata number 292 stomata/mm2, number of epidermis adaxial 1400 epidermis/mm2 and abaxial 1080 epidermis/mm2, apple stomata spread, staple abaxial smaller size 682,560 μm, and stomata index 21,3%.